Gestión para la implementación del SG-SST en empresas de menos de 5 trabajadores en el municipio de Puerto Boyacá Del 2015 Al 2020. - Cerro Davila, Victor Hugo; Torres Pontón, Ivónn María; Nova Gaviria, Vivian Del Pilar (Corporación Universitaria Minuto de Dios, 2020)
Esta tesis de especialización tuvo como objetivo general, resaltar el recorrido histórico del Sistema de Gestión de Seguridad y Salud en el Trabajo en empresas de menos de 5 trabajadores en el Municipio de Puerto Boyacá desde el 2015-2020 Esta investigación se abordó desde el paradigma cualitativo. Expresado su carácter documental y según del primer objetivo específico los capítulos uno y dos ofrecen una aproximación al estado del arte de los SG-SST en Colombia sobre todo en empresas de menos de cinco empleados. Por su parte el capítulo tres presenta la metodología y el diseño del instrumento con base en la normatividad vigente para Colombia teniendo en cuenta las fases del ciclo En el capítulo cuatro evidencia el tercer objetivo específico el cual implica el análisis de los documentos estudiados, se presentan los resultados y la discusión descriptiva con el fin de establecer el grado de cumplimiento en la implementación de los SG-SST en empresas de menos de cinco empleados en el Municipio de Puerto Boyacá. Los resultados indican la existencia de correlaciones positivas y estadísticamente significativas, entre algunas variables de la fase planear con otras variables de las fases hacer, verificar y actuar.

This specialization thesis had the general objective of highlighting the historical journey of the Occupational Health and Safety Management System in companies with less than 5 workers in the Municipality of Puerto Boyacá from 2015-2020 This research was approached from the qualitative paradigm. Expressed its documentary character and according to the first specific objective, chapters one and two offer an approximation to the state of the art of the SG-SST in Colombia, especially in companies with less than five employees. For its part, chapter three presents the methodology and design of the instrument based on current regulations for Colombia, taking into account the phases of the cycle In chapter four the third specific objective which implies the analysis of the documents studied is presented, the results and the descriptive discussion are presented in order to establish the degree of compliance in the implementation of the OSH-OS in companies with less than five employees in the Municipality of Puerto Boyacá. The results indicate the existence of statistically significant and positive correlations between some variables of the planning phase with other variables of the do, verify and act phases. It was also observed that the SG-SST in companies with less than five employees in the municipality of Puerto Boyacá has a process that needs to implement all possible updates, since the planning phase is essential for the work of the SG-SST. It is concluded that companies with less than five employees must better articulate the phases of the PHVA cycle in order to successfully implement the SG-OSH. In other words; Whether the employee or employer is precise and opportune to show from knowing how to recognize through learning to avoid reaching the application of norms that sanction with the economic factor, the same necessary to comply with them; the importance of foreseeing the risk that human beings run when they are repeatedly exposed to the dangers of completing a certain task, since safety can first and foremost help improve health in and outside the workplace. Finally, chapter five reports on the third specific objective, which was to formulate a strategy based on a teaching booklet on the OSH SG as a contribution to the companies that participated in this study. Well, none of the activities that seek the care of life are superfluous; This strategy consisted of games based on the images referring to the risks that can be avoided with a good concentration in the working day
Resaltar el recorrido histórico del Sistema de Gestión de Seguridad y Salud en el Trabajo en empresas de menos de 5 trabajadores en el Municipio de Puerto Boyacá desde el 2015-2020.
Keywords: Sistemas de Gestión; Seguridad y salud en el trabajo; Riesgo laboral; Safety; Safety and Health at Work; Planning; Seguridad en el trabajo; Seguridad social; Sistema de seguridad